Analisis Pengaruh Persepsi Pengetahuan Akuntansi, Penghargaan Finansial dan Pertimbangan Pasar Kerja Terhadap Minat Mahasiswa Jurusan Akuntansi dalam Berkarir Menjadi Akuntan Publik: Studi Kasus Mahasiswa Akuntansi Universitas Tunas Pembangunan, Universita - Amanda Silfa; Supartini; Rahmatya Widyaswati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine whether perceptions of accounting knowledge, financial rewards, and job market considerations influnce accounting student’s interest in choosing a career as a public acoountant. This type of research using primary data obtained from distributing questionnaires both offline and online via Google Form. The population in this study were accounting students from Tuna pembangunan University, AUB Dharma University, and Muhammadiyah Surakarta University in semesters 5 and 7. This research sample used purposive sampling technique to obtain 91 samples. The analytical method used is statistical multiple linear regression analysis processes using SPSS version 25. The results of this research partially ahow that the variables Perseption of Acoounting (X1) and Job Market Considerations (X3) influence students’s interest in pursuing a career as a Public Accountant (Y). Meanwhile, the Financial Rewards variable (X2) has no effect on accounting students’s interest in pursuing a career as a Publik Acoountant (Y).